2020
DOI: 10.1111/ppa.13186
|View full text |Cite
|
Sign up to set email alerts
|

The recombinant isolate of cucurbit aphid‐borne yellows virus from Brazil is a polerovirus transmitted by whiteflies

Abstract: The severe yellowing disease (amarelão) on melon plants is a serious problem in Brazil, although the causative agent remained unknown for a long time. Recently, recombinant isolates of cucurbit aphid‐borne yellows virus (CABYV) were reported as the possible causative agents of this disease on melon plants. Although aphids are known to be the vectors of the common type of CABYV isolates, almost no aphid colony was observed in the major melon fields in Brazil with high incidence of the severe yellowing disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 28 publications
3
44
0
Order By: Relevance
“…B. tabaci is considered a super vector since it transmits over 300 plant viruses including begomoviruses (family Geminiviridae ), criniviruses (family Closteroviridae ), torradoviruses (family Secoviridae ), ipomoviruses (family Potyviridae ), and the carlaviruses CPMMV and melon yellowing-associated virus (MYaV) (family Betaflexiviridae [ 56 , 57 ]). Recently, two poleroviruses (family Luteoviridae ) were also shown to be transmitted by B. tabaci [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…B. tabaci is considered a super vector since it transmits over 300 plant viruses including begomoviruses (family Geminiviridae ), criniviruses (family Closteroviridae ), torradoviruses (family Secoviridae ), ipomoviruses (family Potyviridae ), and the carlaviruses CPMMV and melon yellowing-associated virus (MYaV) (family Betaflexiviridae [ 56 , 57 ]). Recently, two poleroviruses (family Luteoviridae ) were also shown to be transmitted by B. tabaci [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many of the causal viruses are transmitted by whiteflies (Hemiptera: Aleyrodidae), mainly by those belonging to the Bemisia tabaci cryptic species complex. Viruses known to be transmitted by whiteflies include members of the genera Begomovirus , Crinivirus , Ipomovirus , Torradovirus , and Carlavirus ( Navas-Castillo et al, 2011 ), and two poleroviruses (genus Polerovirus ) recently reported to be transmitted by B. tabaci ( Ghosh et al, 2019 ; Costa et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aleurodicus dispersus and Aleurothrixus trachoides each transmit only one virus from the genera Ipomovirus and Begomovirus, respectively, while Trialeurodes vaporariorum and T. abutilonea transmit a few viruses included in the genera Crinivirus and Torradovirus. On the other hand, the Bemisia tabaci complex comprises one of the most important group of plant virus vectors, transmitting over 430 viruses, the majority included in the genus Begomovirus (12,16) but including also viruses classified in the genera Carlavirus, Crinivirus, Ipomovirus, Polerovrius and Torradovirus (12,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%